149k views
4 votes

3(x-4)+3=x-2

User Gordo
by
5.4k points

2 Answers

5 votes


\bf 3(x-4)+3=x-2\implies 3x-12+3=x-2 \\\\\\ 3x-9=x-2\implies 2x-9=-2\implies 2x=7\implies x=\cfrac{7}{2}

User RBreuer
by
4.3k points
4 votes

Answer:

x=3.5

Explanation:

3(x-4)+3 = x-2

Distribute the 3

3x-12 +3 =x-2

Combine like terms

3x-9 = x-2

Subtract x from each side

3x-x -9 = x-2-x

2x -9 =-2

Add 9 to each side

2x-9+9 = -2+9

2x = 7

Divide by 2

2x/2 =7/2

x=3.5

User Bbjay
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.